Method for improving zinc ion transmission performance by adopting Sb-doped TiSe2
By doping Sb in TiSe2, an Sb0.111TiSe2 system was designed, which solved the problem of diffusion between the TiSe2 layers, achieved efficient diffusion of zinc ions and good thermal stability, and improved the rate performance of zinc ions battery .
Patent Information
- Application Number
- CN202411559678.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Zinc ions are difficult to diffuse between TiSe2 layers, resulting in insufficient rate performance of zinc ion batteries.
By doping Sb into TiSe2, the layer spacing is accurately widened, and the optimal Sb-doped TiSe2 system Sb0.111TiSe2 is designed to optimize the diffusion path and energy barrier of zinc ions.
The diffusion energy barrier of zinc ions is significantly reduced, from 0.70eV to 0.26eV, improving the diffusion performance of zinc ions, and maintaining good thermal stability at 300K and 400K temperatures.
Smart Images

Figure CN119517246A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of computational materials science, and in particular relates to a method for improving the zinc ion transport performance of TiSe2 by doping it with Sb. Background Art
[0002] As an energy storage device, zinc-ion batteries have the advantages of high specific capacity, low cost and environmental protection, and have broad application prospects. However, the rate performance of zinc-ion batteries still needs to be further improved. The development of electrode materials with high zinc ion transmission performance is an effective way to solve this problem. Among them, TiSe2 has excellent electronic conductivity, and its special sandwich layered structure provides abundant sites for the adsorption of metal ions and provides a transmission channel for the diffusion of metal ions therein; but due to the large radius of zinc ions, it is still difficult to achieve rapid diffusion in TiSe2. In addition, there is a weak van der Waals force (vdW) between the Se-Ti-Se layers, which provides the premise and basis for realizing the widening of the TiSe2 interlayer; on the other hand, Sb has a large atomic radius, and it has a strong anchoring effect with the Se-Ti-Se layer of TiSe2. Based on this, the present invention proposes a method for Sb-doped TiSe2 to accurately widen its interlayer spacing and designs an optimal Sb-doped TiSe2 system (Sb 0.111 In TiSe2), the diffusion energy barrier of zinc ions is only 0.26 eV, which is significantly lower than its diffusion energy barrier in TiSe2 (0.70 eV). Summary of the invention
[0003] The purpose of the present invention is to provide a method for improving the zinc ion transport performance of TiSe2 by using Sb doping, which provides a theoretical basis and method for improving the rate performance of TiSe2-based zinc ion battery electrode materials. The specific implementation method is carried out according to the following steps:
[0004] Step 1: Use structure search method to identify Sb x TiSe2 and Sb x Ti 1-x Se2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) was screened to obtain its most stable structure;
[0005] Step 2: Calculate and analyze Sb using the CPLAP software package and first-principles method x TiSe2 and Sb x Ti 1-x The formation energy of Se2 varies with the Sb concentration (x), and the Sb x TiSe2 has better structural stability;
[0006] Step 3: Calculate and analyze Sbx The variation of the lattice constant (c) of TiSe2 along the c-axis with the Sb concentration (x);
[0007] Step 4: Calculate Sb x Density of states and energy bands of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278), and analysis of its electronic conductivity;
[0008] Step 5: According to the structural symmetry, construct the zinc ion in Sb x The adsorption structures corresponding to different sites in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) are calculated, and the adsorption energy between them and zinc ions is calculated;
[0009] Step 6: Use the climbing elastic band (CI-NEB) method to search for the Zn ion in Sb x The optimal diffusion path of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) is calculated and compared with its corresponding zinc ion diffusion energy barrier. 0.111 TiSe2 has the best zinc ion diffusion performance;
[0010] Step 7: Use the ab initio molecular dynamics (AIMD) method to study the Sb 0.111 Thermal stability of TiSe2 at 300K and 400K;
[0011] In view of the difficulty of zinc ion diffusion between TiSe2 layers, this paper proposes a method of using Sb-doped TiSe2 to improve its zinc ion transport performance, so as to obtain a design scheme and technical route with an optimal Sb-doped TiSe2 system. First, calculate and analyze the Sb x The intrinsic relationship between the structure, band gap and electronic state density of TiSe2 and the Sb concentration (x); then calculate the Sb x The zinc ion adsorption energy of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) was determined to determine its most stable zinc ion adsorption site; then the climbing elastic band (CI-NEB) method was used to study the zinc ion adsorption on Sb x The diffusion energy barrier of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) varies with the Sb doping concentration, and the optimal Sb-doped TiSe2 system is selected as Sb 0.111 TiSe2, Sb provided by the present invention 0.111 TiSe2 not only has a low zinc ion diffusion barrier (0.26 eV), but also has good thermal stability at temperatures of 300K and 400K. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] By describing in detail the embodiments shown in the accompanying drawings, the drawings described below are only some embodiments of the present invention, in which:
[0013] Figure 1 The overall flow chart of a method for improving the zinc ion transport performance of TiSe2 by doping it with Sb is shown;
[0014] Figure 2 Sb x TiSe2 and Sb x Ti 1-x The formation energy of Se2 (E form );
[0015] Figure 3 The possible diffusion paths of zinc ions in TiSe2 and their corresponding zinc ion diffusion energy barriers;
[0016] Figure 4 For zinc ions in Sb 0.111 Possible diffusion paths in TiSe2 and their corresponding zinc ion diffusion energy barriers;
[0017] Figure 5 For zinc ions in Sb x Variation of diffusion energy barrier in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) with Sb doping concentration (x);
[0018] Figure 6 (a) is Sb 0.111 Total energy of TiSe2 changes with AIMD time (temperature is 300K), Figure 6 (b) is Sb 0.111 The structure of TiSe2 after treatment at 9000fs (temperature is 300K);
[0019] Figure 7 (a) is Sb 0.111 Total energy of TiSe2 changes with AIMD time (temperature is 400K), Figure 7 (b) is Sb 0.111 The structure of TiSe2 after treatment at 9000fs (temperature 400K); DETAILED DESCRIPTION
[0020] This embodiment provides a method for improving the zinc ion transport performance of TiSe2 by doping TiSe2 with Sb, comprising the following steps:
[0021] Sb xTiSe2 is taken as the research object, and the effects of different Sb concentrations (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) on Sb x The structure, electronic conductivity, stability and diffusion barrier of zinc ions in TiSe2 are affected by the energy barrier. x The most stable structure of TiSe2 is calculated, and its band gap and electronic state density are calculated; then the climbing elastic band (CI-NEB) method is used to calculate and compare the Zn ion in Sb x The diffusion energy barrier in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) is used to obtain the optimal zinc ion diffusion path. By comparison, it can be seen that: Sb 0.111 TiSe2 is the optimal Sb-doped TiSe2 system, which has the lowest zinc ion diffusion barrier (0.26 eV). 0.111 Thermodynamic stability of TiSe2. Figure 1 The corresponding overall process of a method of using Sb-doped TiSe2 to improve its zinc ion transport performance is listed.
[0022] The Perdew-Burke-Ernzerh (PBE) method based on the generalized gradient approximation (GGA) is used to treat the exchange correlation energy of electrons, and the projected augmented plane wave (PAW) method is used to describe the interaction between electrons and ions. The valence electrons of Ti, Se, and Zn are 3d 2 4s 2 ,3d 10 4s 2 4p 4 and 3D 10 4s 2 The plane wave cutoff energy of the Ti-Se system and the Ti-Se-Sb system is set to 520 eV. The 3×3×4 and 6×6×8 k-point grids based on the Monkhorst-Pack (MP) type are used for the structural optimization and electronic structure calculation of the TiSe2 system and its Sb-doped system, respectively. The convergence accuracy of force and energy is set to and 10 -5 eV / atom. for Sb x TiSe2 and Sb x Ti 1-x Se2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) was subjected to structural screening to obtain its most stable structure.
[0023] Study on the formation of Sb x TiSe2 and Sb x Ti 1-xThe chemical potential conditions required for Se2 and its optimal Sb doping raw materials. In order to determine the composition of Sb-doped TiSe2 compounds as Sb x TiSe2, respectively calculate and compare Sb x TiSe2 and Sb x Ti 1-x The formation energy (E) of Se2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) form ), the specific calculation steps are as follows: First, calculate the Ti-Se system (including Sb2Se3, Ti 20 (Sb3Se)3, Ti2Sb, Ti5Sb3, Ti3Sb, TiSb2, Ti 13 Sb3 and TiSb) formation enthalpy; then the relative chemical potential of Ti (Δμ Ti ) and the relative chemical potential of Se (Δμ Se ) ranges are: -3.34eV≤Δμ Ti ≤0eV and -1.93eV≤Δμ Se ≤-0.71eV. Then according to Δμ Ti and Δμ Se The value of Sb doped TiSe2 system (Sb x TiSe2) formation energy, and further its optimal growth conditions. x The elemental composition of TiSe2, calculate Sb2Se3, Ti 20 (Sb3Se)3, Ti2Sb, Ti5Sb3, Ti3Sb, TiSb2, Ti 13 The formation enthalpy of Sb3 and TiSb. Based on the formation enthalpy of these compounds and the constraint of the relative chemical potential required for TiSe2, the relative chemical potential of Sb (Δμ Sb ) value; then calculate Sb according to formula (2-1) and formula (2-2) respectively x TiSe2 and Sb x Ti 1-x The formation energy of Se2 (E form ), the calculation results show that with the increase of Sb concentration (x), Sb x The formation energy of TiSe2 is lower than that of Sb x Ti 1-x The formation energy of Se2 indicates that Sb x TiSe2 has excellent structural stability, and Sb is most likely to occupy the octahedral gap between TiSe2 layers. 20 Except for (Sb3Se)3, the other seven Ti-Se compounds can be used as Sb-doped raw materials to synthesize stable Sb xTiSe2. E form =E tot (Sb x TiSe2)-E tot (TiSe2)-x(Δμ Sb +μ Sb ) (2-1) E form =E tot (Sb x Ti 1-x Se2)-E tot (TiSe2)-x(Δμ Sb +μ Sb )+x(Δμ Ti +μ Ti ) (2-2) Where E tot (Sb x TiSe2), E tot (Sb x Ti 1-x Se2) and E tot (TiSe2) respectively represent Sb x TiSe2, Sb x Ti 1-x Total energy of Se2 and TiSe2. x is the Sb concentration or Ti concentration. Δμ Sb and Δμ Ti are the relative chemical potentials of elements Sb and Ti respectively. Ti , μ Se and μ Sb are the total energies of single Ti, single Se and single Sb respectively.
[0024] On this basis, Sb is calculated according to formula (2-3) x The change rate of the lattice constant of TiSe2 along the c-axis (Δc) shows that Sb x The lattice constant of TiSe2 along the c-axis direction increases continuously with the increase of Sb doping concentration (x), which not only provides a suitable storage space for zinc ions, but also provides a driving force for the free diffusion of zinc ions in it. in, and Respectively represent Sb x Lattice constants of TiSe2 and TiSe2 along the c-axis.
[0025] Calculate Sb xThe electronic state density and band gap of TiSe2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) are analyzed to analyze its electronic conductivity. First, consider the spin polarization and calculate the Sb x The total electronic state density of TiSe2 (x = 0.056, 0.111, 0.167, 0.222, 0.278) shows symmetry between the spin-up energy band and the spin-down energy band, which indicates that Sb x TiSe2 has non-spin polarization characteristics; then calculate its band structure and its corresponding partial-wave electronic state density, Sb x The energy bands of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) all cross the Fermi level and have excellent electronic conductivity.
[0026] Determine the zinc ion in Sb x The embedding position of zinc ions in TiSe2 is calculated according to formula (2-4). x The adsorption energy (E) corresponding to different adsorption sites of TiSe2 ad ) It can be seen that zinc ions tend to occupy the octahedral interstitial positions of the Sb-containing layer. in and E Zn Sb x Total energy of adsorption of zinc ions by TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278), Sb x The total energy of TiSe2 and the energy of a single zinc atom.
[0027] The climbing elastic band (CI-NEB) method was used to calculate the Zn ion in Sb x The diffusion energy barrier in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) is used to obtain its optimal diffusion path. x Two adjacent equivalent zinc ion occupied structures of TiSe2 are respectively used as the initial state and the final state in the zinc ion diffusion path, and then the distance between the initial state and the final state is measured, and the number of transition states is set according to this value. x Four transition state structures are inserted between the initial and final states of TiSe2, forming the diffusion path of zinc ions with the initial and final states. x The structural characteristics of TiSe2 and its coordination mode with zinc ions are considered. 0.111 There are two different diffusion paths that may exist in TiSe2 (see Figure 4 Path1 and Path2 in the figure), and then compare the corresponding zinc ion diffusion energy barriers (such as Figure 4 On this basis, the relationship between Sb concentration (x) and Sb x The law between the zinc ion diffusion energy barriers of TiSe2, thus further obtaining Sb 0.111 TiSe2 is the optimal Sb-doped TiSe2 structure, which has the lowest Zn ion diffusion barrier (0.26 eV), which is much smaller than the Zn ion diffusion barrier in TiSe2 (0.70 eV). 0.111 TiSe2 has the best zinc ion diffusion performance. In summary, the present invention proposes that Sb doping TiSe2 is a method for effectively improving its zinc ion diffusion performance.
[0028] Excellent thermal stability is a necessary condition for electrode materials. The ab initio molecular dynamics (AIMD) method was used to further study the Sb 0.111 Thermal stability of TiSe2 at 300K and 400K. Analysis of Sb 0.111 The total energy of TiSe2 at this temperature changes with the AIMD operation time, and its structure after 9000fs treatment is obtained. Figure 6 (a) and Figure 7 (a) It can be seen that at temperatures of 300K and 400K, Sb 0.111 The total energy of TiSe2 shows a stable distribution with AIMD time. Moreover, after heat treatment at 300K and 400K, Sb 0.111 The structure of TiSe2 did not show obvious structural distortion, which further proves that Sb 0.111 TiSe2 has excellent thermal stability at temperatures of 300K and 400K.
[0029] Finally, it is necessary to explain here that the above-mentioned specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above-mentioned contents of the present invention belong to the protection scope of the present invention.
Claims
1. A method for improving the zinc ion transport performance of TiSe2 by doping it with Sb, the method comprising the following steps: Step 1: Use structure search method to identify Sb x TiSe2 and Sb x Ti 1-x Se2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) was used for structural screening to obtain the most stable structure of the two; Step 2: Calculate and analyze Sb using the CPLAP software package and first-principles method x TiSe2 and Sb x Ti 1-x The formation energy of Se2 varies with the Sb concentration (x), and the Sb x TiSe2 has better structural stability; Step 3: Calculate and analyze Sb x The variation of the lattice constant (c) of TiSe2 along the c-axis with the Sb concentration (x); Step 4: Calculate Sb x The density of states and energy bands of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) and analysis of its electronic conductivity; Step 5: According to the structural symmetry, construct the zinc ion in Sb x The adsorption structures corresponding to different sites in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) are calculated, and the adsorption energy between them and zinc ions is calculated; Step 6: Use the climbing elastic band (CI-NEB) method to search for the Zn ion in Sb x The optimal diffusion path in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) and the corresponding diffusion energy barrier are calculated. It is found that Sb 0.111 TiSe2 has the best zinc ion diffusion performance; Step 7: Use the ab initio molecular dynamics (AIMD) method to study the Sb 0.111 Thermal stability of TiSe2 at 300K and 400K.
2. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 1, a structure search method is used to identify Sb x TiSe2 and Sb x Ti 1-x The Se2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) structure was screened to obtain its most stable structure.
3. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 2, the CPLAP software package is used to calculate the formation energy of Sb x The structural stability of TiSe2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278), the specific steps are as follows: Step 2.1: Obtain the structures of Ti-Se compounds (including TiSe, Ti9Se2, Ti8Se3, Ti5Se4, Ti3Se4, Ti2Se, Ti2Se3, Ti 45 Se 16 、Ti 19 Se 20 、Ti 11 Se4 and Ti3Se). Step 2.2: Calculate the formation enthalpy (ΔH) of the Ti-Se compound f ). Step 2.3: Based on the relative chemical potential conditions (Δμ Ti and Δμ Se ), studied the formation of Sb x The growth conditions required for TiSe2, where Δμ Ti and Δμ Se The following conditions should be met (see formulas 1-1 to 1-15): Step 2.4: Use CPLAP software to obtain Δμ Ti and Δμ Se The value range is -3.34eV≤Δμ Ti ≤0eV and -1.93eV≤Δμ Se ≤-0.71eV. According to Δμ Ti and Δμ Se The formation energy of the Sb-doped TiSe2 system is calculated based on the value of, and the chemical potential conditions required to form a stable Sb-doped TiSe2 system are further obtained. Step 2.5: According to Sb x The composition of TiSe2, calculate Sb2Se3, Ti 20 (Sb3Se)3, Ti2Sb, Ti5Sb3, Ti3Sb, TiSb2, Ti 13 The formation enthalpy of compounds such as Sb3 and TiSb, and the determination of the relative chemical potential (Δμ Sb ) value range. Step 2.6: Calculate Sb according to formula (1-16 to 1-17) x TiSe2 and Sb x Ti 1-x The formation energy of Se2 (E form ), and compare the stability of the two. AND form =E tot (Sb x TiSe2)-E tot (TiSe2)-x(Δμ Sb +μ Sb ) (1–16) AND form =E tot (Sb x You 1-x Se2)-E tot (TiSe2)-x(Δμ Sb +μ Sb )+x(Δμ Ti +μ Ti ) (1–17) Where E tot (Sb x TiSe2), E tot (Sb x Ti 1-x Se2) and E tot (TiSe2) respectively represent Sb x TiSe2, Sb x Ti 1-x Total energy of Se2 and TiSe2. x is the Sb concentration or Ti concentration. Δμ Sb and Δμ Ti are the relative chemical potentials of elements Sb and Ti respectively. Ti , μ Se and μ Sb are the total energies of single Ti, single Se and single Sb respectively.
4. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 3, calculate and analyze Sb x The variation law of the lattice constant (c) of TiSe2 along the c-axis direction with the Sb concentration (x); the specific steps are as follows: Step 3.1: Sb obtained in step 1 x The data of the most stable structure of TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) were analyzed to obtain its lattice constant along the c-axis. Step 3.2: Calculate Sb according to formula (1-18) x The change rate of the lattice constant of TiSe2 along the c-axis (Δc) shows that Sb x The lattice constant of TiSe2 along the c-axis direction increases continuously with the increase of Sb doping concentration (x), which not only provides a suitable storage space for zinc ions, but also provides a driving force for the free diffusion of zinc ions in it. in, and Respectively represent Sb x Lattice constants of TiSe2 and TiSe2 along the c-axis.
5. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 4, Sb x The energy band and electronic state density of TiSe2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) structures were calculated to analyze the electronic conductivity of the Sb-doped TiSe2 system; the specific steps are as follows: Step 4.1: Perform static calculations on the TiSe2 and Sb-doped systems obtained in step 1, and set the Brillouin zone k-point grid of the Monkhorst-Pack (MP) type to 6×6×8. Step 4.2: The output file obtained in step 4.1 is used to calculate the energy band and electronic state density of TiSe2 and its Sb-doped system.
6. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 5, according to the structural symmetry, the zinc ion occupies Sb x The adsorption structures corresponding to different sites of TiSe2 are calculated according to formula (1-19) to calculate the corresponding zinc ion adsorption energy (E ad ), it was found that zinc ions tend to occupy the interstitial positions of the octahedron containing Sb layers; in and E Zn Sb x The total energy of adsorption of zinc ions by TiSe2 (x = 0, 0.056, 0.111, 0.167, 0.222, 0.278) and Sb x Total energy of TiSe2 and energy of a single Zn atom.
7. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 6, the climbing elastic band (CI-NEB) method is used to search for the zinc ion in Sb x The optimal diffusion path in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) is obtained. 0.111 TiSe2 has the best zinc ion diffusion performance; the specific steps are as follows: Step 6.1: Obtain the most stable Sb in step 4 x Based on the TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) adsorption zinc ion system, the adjacent equivalent zinc ion adsorption sites are sought. Step 6.2: Sb x The two adjacent equivalent zinc ion adsorption sites of TiSe2 were set as the initial state and final state of its zinc ion diffusion path, and the distance between them was measured; then, according to the relationship between this distance and the transition state spacing, the number of inserted transition states was obtained, thereby designing the zinc ion in Sb x Possible diffusion paths in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278). Step 6.3: Optimization of Zn ion in Sb using the climbing elastic band (CI-NEB) method x The diffusion paths in TiSe2 (x=0, 0.056, 0.111, 0.167, 0.222, 0.278) are obtained, and the corresponding zinc ion diffusion energy barriers are obtained.
8. The method of improving the zinc ion transport performance of TiSe2 by using Sb doping according to claim 1, characterized in that: In step 7, the ab initio molecular dynamics (AIMD) method is used to determine the Sb 0.111 TiSe2 has good thermal stability at both 300K and 400K.
Citation Information
Patent Citations
Process for preparation of absorption layer of solar cell
CN101228639A
Electrically conductive thin film and Electronic device comprising the same
CN105280269A
Method for improving single-layer Mo2C fluorine ion diffusion performance through vacancy induction
CN118083980A
Method for evaluating influence of hydrogen bond substance and Zn < 2 + > on performance of layered positive electrode material
CN118673680A
Lithium and sodium superionic conductors
US20200067131A1